# Solving Exponential Equations

This wiki page is under construction, as part of the Wiki Collaboration Parties. You can help us out by adding examples and explanations.

To solve exponential equations, we need to consider the Rule of Exponents. These rules help us a lot in solving these type of equations.

#### Contents

## Same Base

In solving exponential equations, the following theorem is often useful:

## If \(a\) is a non-zero

constantand \(a^x = a^y,\) then \(x = y.\ _\square\)

We have

\[\begin{align} a^x&=a^y, a\neq 1 \\ \frac{a^x}{a^y} &= 1 \\ a^{x-y} &= 1 \\ x-y &= 0\\ x &= y.\ _\square.

\end{align}\]

Here is how to solve exponential equations:

- Manage the equation using the Rule of Exponents and some handy theorems in algebra.
- Use the theorem above that we just proved.

## Solve \(\displaystyle{ \frac{1}{5^{x-1}} = 125} .\)

Making the bases on both sides equal to 5 gives

\[ \begin{align} \frac{1}{5^{x-1}} &= 125 \\ 5^{-(x-1)}&=5^3 \\ -(x-1) &= 3 \\ x &= -2. \ _\square \end{align} \]

## Solve \( 4^{x-3} = 0.125 .\)

Converting the bases of both sides to 2 gives

\[ \begin{align} 4^{x-3} &= 0.125 \\ 4^{x-3} &= \frac{125}{1000} \\ 2^{2x-6} &= \frac{1}{8} \\ 2^{2x-6} &= 2^{-3} \\ 2x-6&= -3 \\ x&= \frac{3}{2}. \ _\square \end{align} \]

## Find the value of \(x\) when \(4^x = 16.\)

We have \(4^x = 16 \Rightarrow 4^x = 4^2.\) Then the theorem "if \(a\) is a non-zero

constantand \(a^x = a^y,\) then \(x = y\)" gives \(x = 2.\ _\square\)

## \(8^x = 2\), what is \(x\)?

\[\begin{align}

8^x & = 2\\ ({2^3)}^{x} & = 2\\ 2^{3x} & = 2^{1} \end{align}\]

Equating the powers, we get:-

\[\begin{align}

3x & = 1\\ x & = \boxed{\dfrac{1}{3}} \end{align}\]

## If \(6^x - 1=0,\) what is \(x?\)

We have

\[\begin{align} 6^x-1&=0 \\ 6^x &= 1\\ 6^x &= 6^0\\ x &= 0.\ _\square \end{align}\]

## If \((8)(9^x) = 9^x,\) what is \(x?\)

We have

\[\begin{align} (8)(9^x) &= 9^x \\ (8)(9^x) - 9^x &= 0 \\ (7)9^x &= 0 \\ 9^x &= 0. \end{align}\]

Then the theorem "if \(a \neq 0\) and \(a^x=0,\) then \(x = \phi\)" gives \(x = \phi.\ _\square\)

## Different Base

If the bases are different, there are still techniques for solving these exponential equations. If the bases are powers of a common base, we need only convert one or both bases to the common base and proceed using the "Same Base" case.

## Solve \( 4^{3x} =8^{x-1}.\)

We see that while 4 and 8 are different bases, they are both powers of a common base, namely 2. We'll proceed by rewriting 4 and 8 in terms of their common base:

\[ \begin{align} 4^{3x} &= 8^{x-1} \\ (2^2)^{3x} &= (2^3)^{x-1} \\ 2^{6x} &= 2^{3x-3} \\ 6x&=3x-3 \\ x&= -1. \ _\square \end{align} \]

## Solve for x:- \(\dfrac{8^{4x - \sqrt{x}}}{{16}^{2x + \sqrt{x}}} = 2^{2\sqrt{x}}\)

\[\begin{align}

\dfrac{8^{4x - \sqrt{x}}}{{16}^{2x + \sqrt{x}}} & = 2^{2\sqrt{x}}\\ \\ \dfrac{{(2^3)}^{4x - \sqrt{x}}}{{{(2^4)}}^{2x + \sqrt{x}}} & = 2^{2\sqrt{x}}\\ \\ \dfrac{2^{12x - 3\sqrt{x}}}{2^{8x + 4\sqrt{x}}} & = 2^{2\sqrt{x}}\\ \\ 2^{12x - 3\sqrt{x} - 8x - 4\sqrt{x}} & = 2^{2\sqrt{x}}\\ \\ 2^{4x - 7\sqrt{x}} & = 2^{2\sqrt{x}} \end{align}\]

Equating the powers:-

\[\begin{align}

4x - 7\sqrt{x} & = 2\sqrt{x}\\ 4x & = 9\sqrt{x}\\ \sqrt{x} & = \dfrac{9}{4}\\ x & = \boxed{\dfrac{81}{16}} \end{align}\]

## Solve \(\frac{27^{3x-2}}{243} = 81^{3x-6} .\)

Reducing the bases of 27, 81, and 243 on both sides to 3 yields:

\[ \begin{align} \frac{27^{3x-2}}{243} &= 81^{3x-6} \\ \frac{3^{9x-6}}{3^5} &= 3^{12x-24} \\ 3^{9x-6-5} &= 3^{12x-24} \\ 3^{9x-11} &= 3 ^{12x-24} \\ 9x-11 &= 12x-24 \\ 3x &= 13 \\ x &= \frac{13}{3}. \ _\square \end{align} \]

Unfortunately, it won't always be possible to convert to a common base as we did in the examples above.

For instance, in solving \(5^{x} = 3^{x + 2}\), we note that 5 and 3 are not powers of a nice common base. In this case, we'll need to make use of logarithms.

## Solve \(5^{x} = 3^{x + 2}.\)

We have

\[ \begin{align} 5^{x} &= 3^{x + 2} \\ \log_{10}(5^{x}) &= \log_{10}(3^{x + 2}) \\ x\log_{10}5 &= (x + 2)\log_{10}3 \\ x\log_{10}5 &= x\log_{10}3 + 2\log_{10}3 \\ x\log_{10}5 - x\log_{10}3 &= 2\log_{10}3 \\ x(\log_{10}5 - \log_{10}3) &= 2\log_{10}3. \end{align} \]

Therefore, \[x = \frac{2\log_{10}3}{\log_{10}5 - \log_{10}3} \approx 4.3013 .\ _\square\]

## Problem Solving

## \(1728 = 2^a.3^b\), find \(a\) and \(b\)

\[\begin{align}

1728 & = {12}^{3}\\ & = {4 × 3}^{3}\\ & = 4^3 × 3^3\\ & = {(2^2)}^3 × 3^3\\ & = 2^6 × 3^3\\ \therefore a & = \boxed{6}\\ b& = \boxed{3} \end{align}\]

## Solve \(3^{x^2} = 3^{x}.\)

Since both sides of the equation have the same base, their exponents must also be the same:

\[ \begin{align} 3^{x^2} &= 3^{x} \\ x^2 &=x \\ x^2-x&=0\\ x(x-1)&=0\\ \Rightarrow x&=0,1. \ _\square \end{align} \]

## If \( 2^x \cdot 3^y \cdot 5^z = 45,\) what is value of \( x+y+z?\)

Observe that \(45\) can be factorized as follows:

\[ 45 = 3^2\cdot5=2^0\cdot3^2\cdot5^1.\]

Then \(x=0, y=2, z=1,\) which gives \(x+y+z=0+2+1=3.\) \(_\square\)

## If \( x^x \cdot y^y = 108 ,\) what is value of \(x+y ?\)

\(108\) can be factorized as follows:

\[ 108 = 2^2 \cdot 3^3 .\]

This implies that either \(x=2, y=3\) or \(x=3, y=2.\) Therefore the answer is \(x+y=2+3=5. \ _ \square \)

## If \( \frac{2^5}{2^3} \cdot 3^0 \cdot 3^1 \cdot 3^2 = 2^x \cdot 3^y ,\) what is value of \(x+y?\)

\( \frac{2^5}{2^3} \) is expressed as \[ \frac{2^5}{2^3} = {2}^{5-3}=2^2. \qquad (1) \]

\( 3^0 \cdot 3^1 \cdot 3^2 \) is expressed as \[ 3^0 \cdot 3^1 \cdot 3^2 = 3^{0+1+2}=3^3. \qquad (2) \]

From \( (1)\) and \( (2),\) \(x\) and \(y\) are \[ \begin{align} \frac{2^5}{2^3} \cdot 3^0 \cdot 3^1 \cdot 3^2 &= 2^2 \cdot 3^3 \\ &= 2^x \cdot 3^y \\ \Rightarrow x&= 2, y=3. \end{align} \]

Hence, \(x+y= 2+3 = 5. \ _ \square \)

An **exponential equation** is one in which a variable occurs in the exponent. If both sides of the equation have the same base, then the exponents on both sides are also the same:

\[ a^x=a^y \Rightarrow x=y .\]

Here is a list of some rules concerning exponential functions:

\(\qquad (1)~a^m \times a^n = a^{m+n}\)

\(\qquad (2)~a^m \div a^n = a^{m-n}\)

\(\qquad (3)~(a^m)^n = a^{mn}\)

\(\qquad (4)~(ab)^n=a^{n}b^{n}\)

\(\qquad (5)~a^0=b^0\)

\(\qquad (6)~1^m=1^n,\)

where \(a\neq0\) and \(b\neq0.\) Always be cautious of **(5)** and **(6)**; never forget to check if plugging a zero in an exponent works, or if there are any bases that are equal to 1.

**Cite as:**Solving Exponential Equations.

*Brilliant.org*. Retrieved from https://brilliant.org/wiki/exponential-functions-solving-equations/